Analisis Tingkat Kelangsungan Hidup Mangrove untuk Mengukur Keberhasilan Rehabilitasi Mangrove di Desa Tuik Kabupaten Bangka Barat - Ihsan, Ahsanul; Adibrata, Sudirman; Farhaby, Athur Muhammad (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
The mangrove ecosystem in Tuik Village, Kelapa District, West Bangka Regency is one of the coastal areas included in the accelerated mangrove rehabilitation activities. Mangrove rehabilitation carried out in Tuik Village is one of the factors preventing abrasion and improving the economy of coastal communities. This study aims to determine the survival rate of mangroves and the relationship parameters in the success of mangrove rehabilitation. This research was carried out in May-July 2022 in the mangrove rehabilitation area of ​​Tuik Village, Kelapa District, West Bangka Regency. The method used in this study uses a transect line measuring 10m x 10m. Station point determination is divided into five stations using techniquespurposive sampling. The data collected is the number of plants, height, and number of leaves in the transect line. Data is processed and analyzed descriptively and presented in the form of tables, graphs and descriptions. The main component analysis used in data processing is the method (PCA)Principal Component Analysis. The results of research conducted in Tuik Village found two species namelySonneratia andAvicennia, the value ofsurvival rate mangroves with an average range of 10.2 - 10.7%. High growth rate of the speciesSonneratia alba ranges from 0.5 - 1.5 cm, while the growth rate of the species is highAvicennia alba around 1.5 - 1.7 cm. The leaf growth rate of each species is 1 - 2 leaves/month.Survival rate andgrowth rate positively correlated with temperature, current, and sand fraction. The results of the substrate analysis indicated that the speciesSonneratia alba andAvicennia alba shelter on sandy substrate conditions. This shows that the species is able to grow in all types of substrates and has a high tolerance to environmental conditions.